Impact of fluorine on the thermal stability of phlogopite - Sun Jiaqi, Sun Jiaqi; Yang Yan, Yang Yan; Ingrin, Jannick; Wang Zhongping, Wang Zhongping; Xia Qunke, Xia Qunke (The American mineralogist, 2022)
Knowledge of volatile cycling is vital to understanding the evolution of the planet and the life it supports. Although it has been gradually accepted that the mantle is a vast storehouse of H2O and other volatiles, the impact of coexisting volatiles on the thermal stabilities of OH and the lattice of the host mineral is still poorly understood. Phlogopite is one of the few hydrous minerals capable of carrying both water and halogens into the mantle. Previous observations from both experiments and textural relationships in natural samples have indicated that F-rich phlogopite can be stable under ultrahigh-temperature conditions. Here, the impact of F on the thermal stability of phlogopite was investigated via XRD, Raman, and IR spectroscopy from room temperature to 1000 to 1200°C. Based on the experimental results from F-poor and F-rich natural phlogopites, we show that about 4 wt% F can increase the breakdown temperature of phlogopite by 100°C under ambient pressure. The impact mechanism mainly involves preventing OH and lattice softening at high temperatures. This study reveals the links between F and the behavior of OH and phlogopite lattice, which is important for constraining volatile cycling, as well as the role of F in the physical and chemical properties of the upper mantle.